Embedded Academic Librarians Instilling Life-Long Learning Skills: A Proposed Methodology for Assessing Self-Perceived Information-Seeking Behaviors of Undergraduate Students - Gonzalez, Adriana (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
As librarians, we want to believe that we impact information-seeking behaviors of students and instill a desire to continue learning.  While many institutions collect student feedback from students taking library instructional classes, there is not always a clear indicator of the role librarians have in shaping information-seeking behaviors.  With the growing number of embedded librarians, there is a growing need to assess how information-seeking behaviors are changing.  These teaching opportunities and atypical model for library instruction may potentially have a different impact on student research behavior over time.  Therefore, this paper proposes a methodology to begin assessing how undergraduate students perceive their information-seeking behavior development.